The role of NLRP3 inflammasome in hepatocellular carcinoma - Zhao, Huijie; Zhang, Yiming; Zhang, Yanting; Chen, Chaoran; Liu, Huiyang; Yang, Yihan; Wang, Honggang (Frontiers in Pharmacology, 2023)
Inflammasomes play an important role in innate immunity. As a signal platform, they deal with the excessive pathogenic products and cellular products related to stress and injury. So far, the best studied and most characteristic inflammasome is the NLR-family pyrin domain-containing protein 3(NLRP3) inflammasome, which is composed of NLRP3, apoptosis associated speck like protein (ASC) and pro-caspase-1. The formation of NLRP3 inflammasome complexes results in the activation of caspase-1, the maturation of interleukin (IL)-1β, and IL-18 and pyroptosis. Many studies have demonstrated that NLRP3 inflammasome not only participates in tumorigenesis, but also plays a protective role in some cancers. Hepatocellular carcinoma (HCC) is a major cause of cancer-related mortality. The persistent poor prognosis of HCC can be attributed to the late diagnosis, while there are few effective treatment options. Therefore, it is particularly urgent to explore the pathogenesis of HCC and find an effective treatment. The increasing evidence indicate that NLRP3 inflammasome plays a vital role in HCC, however, the related mechanisms are not fully understood. Hence, we summarized the literatures on the role of NLRP3 inflammasome in HCC in recent years, and analyzed the relevant mechanisms in detail to provide reference for future in-depth researches.